STUDI KASUS PENERAPAN ASAS KERAHASIAAN DI MADRASAH TSANAWIYAH SWASTA MADINATUSSALAM SEI ROTAN - Khairuddin Tambusai; Dewi jayanti (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2018)
The purpose of this study is to find out about How to Understand the Principle of Confidentiality of BK Teachers, How to Implement the Principle of Confidentiality in Private Madrasah Tsanawiyah Madinatussalam Sei Rotan, What Factors Support and Inhibit Implementation of the Principle of Confidentiality in Private Madrasah Tsanawiyah Madinatussalam Sei Rotan. This research uses qualitative research design with case study approach. Data collection techniques in this study using observation, interviews, and documents. Data analysis using Milles and Huberman data analysis model are: data reduction, data presentation, and conclusion/verification. And check the validity of data in this study using the criteria of creadibility confidence that is: Longer attachment, diligence observations in research, and triangulation testing. The findings show that: (1) An understanding of the principle of secrecy of BK Madrasah Tsanawiyah Madinatussalam Sei Rotan teachers, including: (a) Maintaining trust and maintaining confidentiality. (b) Commit to ensuring the confidentiality of all the problems faced by the students. (2) Application of the principle of confidentiality in Madrasat Madanatussalam Sei Rotan Madrasah, it can be seen that the application of the principle of confidentiality in madrasas includes: (a) Asking for willingness, (b) Providing direction, (c) Making approaches, (d) Making agreements, (e) Motivating, (f) Providing solutions. (3) Factors that support the application of secrecy principles in Madrasah Tsanawiyah Madinatussalam Sei Rotan, including cooperation between the teachers and students, make arrangements, secret custody. While the inhibiting factors of application of the principle of secrecy include: (a) Lack of infrastructure supporting the activities of BK.Keywords: Secrecy Principle